PENGARUH KETERGANTUNGAN ENERGI FOSIL TERHADAP KETAHANAN ENERGI NASIONAL DI INDONESIA - Syawal Sihite; Zuraidah Tharo; Dino Erivianto (Jurnal Nasional Teknologi Komputer, 2025)
This study aims to untangle the influence of fossil energy dependence on national energy security in Indonesia. Using a qualitative descriptive approach and literature study as data collection methods, this study examines the actual conditions of the national energy mix, the challenges of the energy transition, and its impact on four dimensions of energy security: availability, accessibility, affordability, and affordability. The results of the study indicate that the dominance of fossil energy in the national energy system causes energy supply vulnerability, distribution inequality, burdens due to fiscal subsidies, and increased carbon emissions. On the other hand, the government's commitment to increasing the portion of renewable energy has not been optimally achieved. Therefore, a more progressive and integrated energy transition strategy is needed to strengthen national energy security. This study contributes as a basis for analyzing more sustainable energy policies in the future.